TINJAUAN TARIF INDONESIAN CASE BASE GROUPS (INA CBGs) DAN TARIF RUMAH SAKIT PADA PASIEN RAWAT INAP KASUS BEDAH ORTHOPEDI PESERTA BPJS DI RUMAH SAKIT UMUM KABUPATEN TANGERANG - Happy Novriyanti Purwadi; Kamaluddin Latief; Vannya Dwi Nurlita (STIKes IMC Bintaro, 2018)
Introduction. The changing of claim system in National Health Insurance (JKN) era give an impact to hospital income. Payment system to change the payment system prospective known as casemix (case based payment). Casemix system is the payment system healthcare services package where payments or it is determined given before service. But this has not been effective because with the tariff of INA CBGs potentially creates losses for hospital. This study attempts to tell the difference mean hospital tariffs and INA CBGs tariffs based on several factors namely: code icd 10, long care, in class, severity level and kind of action. Method. The study use a quantitative with calculation of the total cost of the average and Mann Whitney. Results. Mean hospital tariffs larger of INA CBGs tariff. Mean the hospital tariffs Rp. 16.069.741 and mean tariff Ina CBGs Rp. 15.088.149. The main diagnosis of most cases in orthopedic surgery is Diabetes Mellitus as many as 26 cases (15.11%) with an average length of stay more than 7 days. At the severity level I and the type of minor surgery there are 130 cases with a negative difference Rp. 36.273.00, on the severity level II and the type of surgery is there are 30 cases with a negative difference Rp. 7.884.074, on the severity level III and type of heavy surgery there are 12 cases with positive difference Rp. 5.369.891 whereas in the type of class I there is a negative difference Rp. 3.253.380, class II there is a positive difference Rp. 112.768.00 and class III there is a negative difference Rp. 438.566.00. Conclusion. From 172 cases there was a negative difference between hospital tariffs and INA CBGs tariffs. Advice. For the hospital build a team quality control and cost containment, increase efficiency.